La dama de oro - Brühl, Daniel; Mirren, Helen, 1945-; Speak Up (Barcelona RBA revistas, 2015)
Maria Altmann, an octogenarian Jewish refugee, takes on the Austrian government to recover artwork she believes rightfully belongs to her family.
Helen Mirren, Daniel Brühl, Ryan Reynolds, Antje Trauer, Tatiana Maslany
No recomendada para menores de 7 años
Acompaña a la revista Speak Up no. 365
Idiomas : Inglés y castellano. Subt.: inglés (subtítulos speak up) y castellano
Keywords: Películas cinematográficas -- DVD